Exploring the function of protein kinases in schistosomes: perspectives from the laboratory and from comparative genomics - Walker, Anthony J.; Ressurreição, Margarida; Rothermel, Rolf (Frontiers in Genetics, 2014)
Eukaryotic protein kinases are well conserved through evolution. The genome of Schistosoma mansoni, which causes intestinal schistosomiasis, encodes over 250 putative protein kinases with all of the main eukaryotic groups represented. However, unraveling functional roles for these kinases is a considerable endeavor, particularly as protein kinases regulate multiple and sometimes overlapping cell and tissue functions in organisms. In this article, elucidating protein kinase signal transduction and function in schistosomes is considered from the perspective of the state-of-the-art methodologies used and comparative organismal biology, with a focus on current advances and future directions. Using the free-living nematode Caenorhabditis elegans as a comparator we predict roles for various schistosome protein kinases in processes vital for host invasion and successful parasitism such as sensory behavior, growth and development. It is anticipated that the characterization of schistosome protein kinases in the context of parasite function will catalyze cutting edge research into host-parasite interactions and will reveal new targets for developing drug interventions against human schistosomiasis.